A arte imita a vida: um estudo sobre informação e cidadania a partir da ficção em HQs, mangás e animes - Cavalcante, Stefano Souza (Brasil, 2023)
The present work discusses the use of graphic and audiovisual narratives as sources of influence and its consequent form of reflection on information and citizenship in reality, using comics, manga and anime as objects of study. The main objective of the research is to investigate the influence that these fictional works have on society, focusing on topics related to information and citizenship. It is justified by the little exploration of the theme in scientific research in the area of Librarianship, as well as demonstrating the importance that such works have as sources of debates for relations of information and citizenship. For this, the discourse analysis method is used, taking into account that the discourse contained in the works was fundamental in the data collection, appearing both in textual form and in representations. The results and discussions point to a strong contextualization of reality being placed in fiction, with the materials presenting relevant discussions in our society. With that, it is expected that this research will be used for more studies that are similar to those contained here, as well as showing how comics, manga and anime can be important for scientific analysis.